Pandemija COVID-19 in možganskožilne bolezni - Bizovičar, Nataša (Rehabilitacija (Ljubljana), 2021)
Background: The COVID-19 pandemic has placed a heavy burden on health systems. COVID-19 may affect rehabilitation treatment directly, as the infection increases the risk of stroke, or indirectly due to difficult patient care. The aim of the study was to determine how we performed outpatient and inpatient services at the Department for rehabilitation of patients after stroke during the first and part of the second wave of the COVID-19 epidemic. Methods: The study retrospectively reviewed medical records of patients from March to December 2020. We collected the number of examined patients in subspecialist (SUB) and triage outpatient clinic (TRI), the number of cancelled examinations, the number of outpatient applications of Botulinum toxin, testing and delivery of wheelchairs. For hospital patients, we collected general patient and stroke data. To compare numerical variables between the two years, we used the t-test for independent samples, and the chi-squared test for differences in the proportions of categorical variables. Results: From the beginning of the epidemic until the end of 2020, we examined 12.8% fewer patients in TRI and 17.8% fewer patients in SUB than in 2019. In 2020, we performed 8.8% more outpatient applications of Botulinum toxin and 10.8% fewer outpatient tests and deliveries of wheelchairs/scooters than in 2019. In 2020, we treated 15.1% fewer inpatients than in 2019. Conclusions The COVID-19 epidemic has caused major changes in the inpatient and outpatient treatment of patients after stroke. There are ongoing challenges between providing rehabilitation services and reducing the risk of infection transmission. The consequences of the epidemic on patients after stroke are likely to be even more pronounced in 2021, therefore the experience so far with adjustments to the implementation of rehabilitation is important for the best possible care of these patients.
Keywords: COVID-19; možganska kap; pandemic; pandemija; rehabilitacija; rehabilitation; Stroke